Civic Education in Digital Era: Implementing Pancasila Values for Generation Z College Students - Salwa Anggraeni Khriswina; Setiawan Edi Wibowo; E Kus Eddy Sartono (STAI Hubbulwathan Duri, 2025)
This study explores how Generation Z students in the Primary School Teacher Education (PGSD) program embody the values of Pancasila in the digital era, particularly through civic education courses and their integration into positive, everyday activities. Using a qualitative research design with a case study approach, data were collected through semi-structured interviews. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the rapid advancement of digital technology and modernization has not weakened the commitment of Generation Z students to uphold and practice Pancasila values. Students continue to reflect these values in both academic and non-academic settings. Civic education in higher education serves as a reinforcing medium, allowing students to internalize and express the principles of Pancasila—such as unity, social justice, and democracy—through digitally enhanced platforms and activities. Despite living in a highly digitalized environment, Generation Z PGSD students remain grounded in the ideology of Pancasila. Civic education courses, when adapted to modern technological contexts, are effective in maintaining the relevance of national values. These findings highlight the potential for civic education to bridge traditional ideological foundations with contemporary student lifestyles.